2017
DOI: 10.11613/bm.2017.032
|View full text |Cite|
|
Sign up to set email alerts
|

Does small equal predatory? Analysis of publication charges and transparency of editorial policies in Croatian open access journals

Abstract: IntroductionWe approach the problem of "predatory" journals and publishers from the perspective of small scientific communities and small journals that may sometimes be perceived as "predatory". Among other characteristics of "predatory" journals two most relevant are their business model and the quality of the editorial work.Materials and methodsWe analysed 444 Croatian open access (OA) journals in the Hrčak (portal of Croatian scientific journals) digital journal repository for the presence of article proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The journal's scope is too broad, covering almost all fields of science 37 Publishing ethics and standards Research and publishing ethics are not followed; reviewing, editing and or indexing services are not provided 16,19 Indexing Predatory publishers claim to have their articles indexed, while they are, in fact, not indexed in any important databases such as MEDLINE, PubMed and Web of Science 40 Copy-editing and spelling errors Published articles are poorly copy-edited and contain numerous typographical or grammatical errors. In addition, such errors can be found on the journal's website, which also commonly include dead links 22 Submission system Predatory journals ask authors to send their manuscripts by email, instead through a professional manuscript submission system 32 Table 3 Criteria to receive the Seal of Approval for Open Access Journals (DOAJ Seal) by the Directory of Open Access Journals (DOAJ)…”
Section: Scopementioning
confidence: 99%
See 1 more Smart Citation
“…The journal's scope is too broad, covering almost all fields of science 37 Publishing ethics and standards Research and publishing ethics are not followed; reviewing, editing and or indexing services are not provided 16,19 Indexing Predatory publishers claim to have their articles indexed, while they are, in fact, not indexed in any important databases such as MEDLINE, PubMed and Web of Science 40 Copy-editing and spelling errors Published articles are poorly copy-edited and contain numerous typographical or grammatical errors. In addition, such errors can be found on the journal's website, which also commonly include dead links 22 Submission system Predatory journals ask authors to send their manuscripts by email, instead through a professional manuscript submission system 32 Table 3 Criteria to receive the Seal of Approval for Open Access Journals (DOAJ Seal) by the Directory of Open Access Journals (DOAJ)…”
Section: Scopementioning
confidence: 99%
“…35,36 The titles of such journals often sound quite ambitious and include words such as 'Innovative', 'World', 'International', 'Global', 'American', or 'European', covering almost all scientific areas. 37 Another disturbing trend is the fact that cybercriminals register a domain name in order to create fraudulent websites for a counterfeit journal, which are designed to look identical to those of a legitimate scientific journal ('hijacking'). 38 Does the journal follow the COPE Code of Conduct for Journal Publishers?…”
Section: Doaj Seal Criteriamentioning
confidence: 99%
“…The criteria ensure the high quality of Croatian journals. Quality control is mainly enacted through the traditional concept of peer review, mostly double-blind review by two peer reviewers (Stojanovski & Marušić, 2017). Before a journal is allowed to be listed on the Hrčak portal, its editorial process (including peer review) is evaluated.…”
Section: Scientific Journals In Croatiamentioning
confidence: 99%
“…Zrinščak () investigated editorial policies in the social sciences scientific journals in Croatia and found that scientific journals need editors with substantial experience in editing and reviewing, as well as more professionalism, and that the quality of the peer review process in investigated social sciences scientific journals differed from case to case. The study about the peer review process written by Stojanovski and Marušić () analysed 444 Croatian open access journals and found that the transparency of the peer review process was not high.…”
Section: Introductionmentioning
confidence: 99%